DESAIN PENGEMBANGAN KURIKULUM MADRASAH ALIYAH UNGGULAN DI ERA REVOLUSI INDUSTRI 4.0 - Mochamad Nurcholiq (STAI Ma'had Aly Al-Hikam Malang, 2019)
Madrasah Aliyah (Islamic Junior High School) is an educational institution that has specificity in ideas and applications to manifest Islamic values embodied in vision, mission, goals, and educational programs. Madrasah Aliyah graduates are expected not to miss the era of industrial revolution 4.0 which emphasizes the pattern of digital economy, artificial intelligence, big data, robotic, or known as the disruptive innovation phenomenon. Leading graduates of Madrasah Aliyah are prepared to become quality cadres or human resources with high competitiveness. Curriculum design is a core part of education that must have the right guidelines and objectives in accordance with the socio-cultural conditions of the community and keep up with the times like the current of industrial revolution era 4.0.Â Madrasah Aliyah merupakan lembaga Pendidikan memiliki kekhususan dalam ide dan aplikasi untuk memanifestasikan nilai-nilai Islam yang diwujudkan dalam visi, misi, tujuan, maupun program pendidikan. Lulusan Madrasah Aliyah diharapkan tidak ketinggalan pada era revolusi industri 4.0 yang menekankan pada pola digital economy, artificial intelligence, big data, robotic, atau dikenal dengan fenomena disruptive innovation. Lulusan Madrasah Aliyah unggulan disiapkan menjadi kader atau sumber daya manusia yang berkualitas serta memiliki daya saing yang tinggi. Desain kurikulum merupakan bagian inti dari pendidikan yang harus memiliki pedoman dan tujuan yang tepat sesuai dengan kondisi sosial budaya masyarakat dan mengikuti perkembangan zaman seperti era revolusi industry 4.0 saat ini.